Chapter 31: Linking smallholder producers to market: the need for efficient supply chain management - Batt, Peter J (Scientific Publishers, 2022)
With increasing affluence and the expansion of modern retailing and food processing, fresh produce buyers are forging enduring long-term relationships with their preferred suppliers. Such relationships provide customers with assurances that the product will be delivered on time, in the quantities required, to predetermined specifications which govern not only the product quality but the manner in which the product has been produced. For the buyers, such relationships reduce transaction costs, there is less wastage, and risk and uncertainty are greatly reduced. For the suppliers, such relationships provide an assured market but they do not always guarantee a higher price. Such relationships will only develop where there is an equitable sharing of value in the exchange, an element of trust and a long-term commitment. Invariably, for smallholder producers, their participation in such value-added chains is contingent upon the formation of formal or informal groups, thereby providing some economies of scale and a greater capacity to meet the needs of their downstream customers. Trust and social capital is instrumental in the formation of these groups. Trust and satisfaction in the exchange will be derived primarily from the knowledge that smallholder producers are not being taken advantage of by downstream market intermediaries. This will require market intermediaries to provide timely information on market prices and where appropriate, technical advice and micro-finance to facilitate production. However, there is always the risk that smallholder producers will forgo long-term relationships to secure immediate short-term benefits by transacting with alternative buyers who offer a higher price. Furthermore, on occasions, it may be necessary for smallholder producers to transact with alternative buyers to dispose of that product which fails to meet specifications and/or where the collapse of failure of the focal customer leaves smallholder producers without a buyer. Various mechanisms are available to provide a degree of flexibility and at the same time, to ensure that contractual obligations are fulfilled. Thus, it is not only possible but indeed desirable for these value-added chains to co-exist in parallel with traditional supply chains. Ultimately, for smallholder producers to participate in these modern value-added chains there must be a willing buyer who is able to pay a price that is sufficient to adequately compensate the producer. With such an assurance, collaborative farmer groups can confidently embark upon a production plan to maintain sufficient supply. However, smallholder producers must have access to the desired technologies, agronomic advice and finance to secure good quality seed, chemicals and fertilisers, and downstream buyers must refrain from the use of coercive market power, for this will have a significant negative impact on trust and smallholder producers’ commitment to the relationship.